Prevalence of Complete Streets policies in U.S. municipalities. (June 2017) - Carlson, Susan A.; Paul, Prabasaj; Kumar, Gayathri; Watson, Kathleen B.; Atherton, Emiko; Fulton, Janet E.
Abstract: Communities can adopt Complete Streets policies to support physical activity through the routine design and operation of streets and communities that are safe for all people, regardless of age, ability, or mode of transport. Our aim was two-fold: (1) to estimate the prevalence of Complete Streets policies in the United States overall and by select municipality characteristics using data from the National Survey of Community-Based Policy and Environmental Supports for Healthy Eating and Active Living (CBS HEAL) and (2) examine the agreement between information about local policies reported in CBS HEAL with those found in the National Complete Streets Coalition's database. Data from a representative sample of incorporated U.S. municipalities with a population of at least 1000 people (n = 2029) were analyzed using survey weights to create national estimates. In 2014, 25.2% of municipalities had a Complete Streets policy reported by a local official. Prevalence of local policies decreased with decreasing population size and was lower among those with a lower median education level and those in the South, with and without adjustment for other municipality characteristics. Agreement between local Complete Streets policies reported in CBS HEAL and the coalition's database was moderate with 72.5% agreement (kappa = 0.21); however, agreement was lower for municipalities with smaller populations, those located in rural areas, and those with a lower median education level. About 16.8% of local officials reported they did not know if their municipality had such a policy. There is room for improvement in the awareness and adoption of Complete Streets policies in the United States, especially among smaller municipalities and those with lower median education levels. Helping communities address issues related to the awareness, adoption, and implementation of Complete Streets policies can be an important step toward creating more walkable communities. Highlights: Complete Streets policies support physical activity. 25% of municipalities had a Complete Streets policy reported by a local official. Differences in local policies exist by size, median education, and region. Agreement for local policies between survey reports and the database was moderate. Room for improvement in the awareness and adoption of Complete Streets policies.